Corneal side effects induced by EGFR-inhibitor antibody–drug conjugate ABT-414 in patients with recurrent glioblastoma: a prospective clinical and confocal microscopy study - Parrozzani, Raffaele (Ther Adv Med Oncol, 2020)
BACKGROUND: The aim of this study was to prospectively analyse, for the first time worldwide by in vivo clinical confocal microscopy (CCM), corneal side effects secondary to the use of epidermal growth factor receptor (EGFR) inhibitor depatuxizumab mafodotin (ABT-414) in a cohort of patients affected by EGFR-amplified recurrent glioblastoma. METHODS: Each enrolled patient underwent full ophthalmologic examination including in vivo CCM of the cornea. Each patient was examined at baseline and every 2 weeks during treatment as long as patient conditions allowed it. RESULTS: A total of 10 patients were consecutively enrolled. Median follow-up was 5 months. No Common Terminology Criteria for Adverse Events Version 4.0 grade 4 toxicity was documented. Two (20%) grade 3 toxicities were documented at week 8. CCM examination detected in all eyes multiple and diffuse hyperreflective white round spots in the corneal basal epithelial layers (100%), progressive subbasal nerve plexus layer fibres fragmentation followed by full disappearance (100%) and appearance of round cystic structures in the corneal epithelium (100%). All CCM documented side effects reached the peak of prevalence and severity after a median of 3 infusions. After treatment discontinuation, the reversibility of corneal side effects was documented at CCM after a median of 4 weeks. CONCLUSION: ABT-414 toxicity is not only directed to the corneal epithelium, but also to corneal nerves. Side effects are detectable in all treated patients and CCM documents early corneal epithelium and subbasal nerve plexus toxicity, with subsequent progressive restoration after treatment discontinuation. Ocular side effects due to ABT-414 can be manageable.